Analysis and Design of a Web Connection in Direct Tension - Anand, Subhash C.; Bertz, Richard F. (Engineering Journal, 1981)
Light bracing composed of a tension plate welded to the web of a column or beam section is employed quite often in the design of steel structures. Generally, the strength of a web in carrying the tensile load is of primary concern. There are two analysis procedures which have been suggested for the strength analysis of the web. The first is an elastic method suggested by Blodgett, and the second, an ultimate strength yield line method proposed by Kapp. Experimental tests have indicated that the strength of these connections are, in general, much greater than the strength predicted by either the elastic or the yield line theories. Therefore, a study was undertaken to further investigate the behavior of this connection type in the plastic range by use of the finite element technique.